259 A case of lymphoepithelioma-like carcinoma in the uterine cervix. (18th September 2019) - Sert, MB; Nesbakken, AJ; Paulsen, T
Abstract : Objectives: To find a relationship between human papillomavirus (HPV 16)/Epstein-Barr virus (EBV) and cervical lymphoepithelioma-like carcinoma (LELC) in a uterine cervix case. Methods: In this a rare case report, we present a 56 years of Norwegian woman with (FIGO 2009) stage IB1 LELC in the uterine cervix. We described the clinical and histopathologic findings in detail and in addition to that we also analysed the Epstein- Barr virus (EBV) and Human papilloma virus (HPV) by using the relevant proper techniques in order to identify the real underlying pathogenesis. LELC case was first reported almost 50 years ago in the world literature and this is one of the very few case reported in scandinavia. 2 years after Piver type III open radical hysterectomy she has been living well without any complains and recurrence. Her rutine control has increased to 6 months interval. Results: Epstein-Barr virus analysed by in situ hybridization (ISH) which was negative in this case. On the other hand HPV 16 test was positive. Pasient Conclusions: This rare case report supports a possible different pathway of pathogenesis of cervical LELC in a Norwegian woman. The exact role of EBV and HPV in the development of LELC tumour is remains to be defined.